Adoption potential of black soldier fly (Hermetia illucens (L.), Diptera: Stratiomyidae) larvae composting technology among smallholder farmers in Greater Ahafo-Ano, Ashanti region of Ghana - Dzepe, D.; Osae, M.Y.; Asabre, J.O.; Twumasi, A.; Ofori, E.S.K.; Atampugre, G.; Abdoulaye, T.; Asiedu, R.; Djouaka, R. (Elsevier, 2024)
As the world’s population increases, the growing demand for food intensifies the generation of agricultural waste, leading to several environmental issues. Intensive research indicates black soldier fly (BSF) larvae Hermetia illucens (Linnaeus, 1758) as efficient converters of organic waste into nutrient-rich biomass suitable for animal feed. Using a structured questionnaire and volunteer farmers (N = 595), we investigated the potential for adoption of BSF larvae composting technology for sustainable agricultural waste management in Greater Ahafo-Ano. Almost all surveyed farmers declared they generated a significant amount of biowaste on their farms and were willing to learn how to use the BSF-based technology to transform it into value-added products. The waste generated was mainly disposed of in pits at Ahafo-Ano South-East (56.2%), by composting at Ahafo-Ano South-West (34.9%) and by sale at Ahafo-Ano North (34.4%). Across the three districts, awareness of the BSF was very low – 14.5% in Ahafo-Ano South-East, 14.1% in Ahafo-Ano South-West and 0.5% in Ahafo-Ano North. However, high acceptance of the technology was recorded. It was found that about 8% of farmers surveyed in Ahafo-Ano South-East had already tried BSF farming on a small scale. Indicating this district as a good entry point to introduce the technology into Greater Ahafo-Ano.